Pengaruh Exchange Rate, Inflasi, Risiko Sistematis Dan BI Rate Terhadap Return Saham Syariah Di Jakarta Islamic Index (JII) Periode 2015-2018 - Abdul Jabar, Ahmad Karim; Cahyadi, Iwan Fahri (IAIN Kudus, 2020)
This research aims to determine the effect of variable exchange rate, inflation, systematic risk, and bi rate partially on the return of sharia stocks in the Jakarta Islamic Index (JII). In addition, to know the effect of variable exchange rate, inflation, systematic risk, and BI rate simultaneously on the return of sharia stocks in Jakarta Islamic Index (JII) period 2015-2018. This type of research is quantitative research with secondary data sources. The sampling method uses the purposive sampling method. This research data uses sharia stock data listed in Jakarta Islamic Index period 2015-2018. The method of data analysis used is to use multiple linear regression analysis methods. The results of this study show that partially variable exchange rate (X1) negatively and significantly affects the return of sharia stocks with a value of t-count > t-table (2.482 > 1,998) and a significant rate of 0.016 > 0.05, while inflation also negatively and significantly affects the return of sharia stocks with a value of t-count > t-table (2,600 > 1,998) and a significant level of 0.012 < 0.05, and systematic risk (X3) affects the return of sharia stocks with a value of t-count > t-table (2.038 > 1.998) and a significant level of 0.046 < 0.05, while the BI rate (X4) negatively and significantly affects the return of sharia stocks, with a value of t-count > t-table (2.412 > 1,998) and a significant level of 0.019 < 0.05. Simultaneously indicates that the exchange rate, inflation, systematic risk, and BI rate significantly affect the return of sharia stocks with a value of F-count > F-table (2.810 > 2.52) with a significance value of 0.033.